ESTIMASI PENYESUAIAN LIKUIDITAS PADA VALUE AT RISK DARI DATA HISTORIS - , Noviana Pratiwi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Investment always has a risk. Volatility of return is connected with risk. investor required risk measurement to managing risk. Value at Risk (VAR) is a risk measurement techniques and considered as a standard method of measuring risk. In determaining how big the risk target, Investor use VaR. In portfolio, VaR is defined as the estimated of maximum loss will be faced by the portfolio at a spesific time period within a certain confidence level. There are three main methods to calculate the VaR i.e. variance-covariance method, historical simulation method and monte carlo simulation method. Capital market are not one hundred percent liquid, but VaR model is usually asumsed to be liquid market. Whereas market liquidity should be considered in capital market due to be role optimally in supporting economic growh, the market must be liquid. There is the liquidity risk in the market, if liquidity risk has joined VaR models then VaR increases. Incorporation of likuidity risk into VaR model is called Liquidity adjuated Value at Risk (LVaR). Last chapter will be give empirical analysis of VaR and LVaR calculation on two portfolio wich separated besed on liquidity risk value for comparing the risk level from less liquidity portfolio and high liqyidity portfolio.